2020
DOI: 10.3390/ma13204537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Groove and Steel Fiber on Shear Properties of Concrete with Recycled Coarse Aggregate

Abstract: In this paper, a series of shear specimens with or without groove were manufactured to mainly analyze the effects of grooves (or shear section height) and steel fibers on the shear properties of concrete with recycled coarse aggregate through double-side direct shear test. In addition, the relationship between the shear strength and the compressive strength and splitting tensile strength of steel fiber reinforced concrete with recycled coarse aggregate (SFRCAC) was also discussed. The experimental results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Additionally, all developed HyFRC specimens showed quasi-brittle characteristic with a strain-softening mode of failure under the direct shear. Similar findings have also been reported in other studies [ 31 , 36 ]. Figure 6 superimposes the density on the shear strength of all HyFRC specimens, which revealed that a proper, consistent mix was achieved during the casting of the HyFRC with no effect on the shear strength results.…”
Section: Resultssupporting
confidence: 93%
“…Additionally, all developed HyFRC specimens showed quasi-brittle characteristic with a strain-softening mode of failure under the direct shear. Similar findings have also been reported in other studies [ 31 , 36 ]. Figure 6 superimposes the density on the shear strength of all HyFRC specimens, which revealed that a proper, consistent mix was achieved during the casting of the HyFRC with no effect on the shear strength results.…”
Section: Resultssupporting
confidence: 93%
“…Shi et al believed that pretreatment of RA by carbonization is environmentally friendly and effective [ 21 ]. The use of biotreatment or the incorporation of steel fiber and nanosilica can improve both the mechanical properties and microstructure of RAC [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, Figure 14 shows that the fitting coefficients are sufficient for satisfying the requirement. To verify the reliability of Equations (7)–(9), the data of Gao [ 33 , 34 ], Carneiro [ 35 ], Yazc [ 36 ], Ahmadi [ 37 ], and Kachouh [ 38 ] were used to compare the calculation results of the formula with the test results. The results are listed in Table 7 .…”
Section: Resultsmentioning
confidence: 99%